2022
DOI: 10.1186/s13018-022-03440-7
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors for surgical site infection following volar locking plating (VLP) of unstable distal radius fracture (DRF)

Abstract: Purpose Volar locking plating (VLP) is the mainstay of treatment for distal radius fracture (DRF) but may be compromised by postoperative surgical site infection (SSI). This study aimed to identify the incidence and the risk factors for SSI following VLP of DRF. Methods This retrospective study identified consecutive patients who underwent VLP for closed unstable DRFs in our institution between January 2015 and June 2021. Postoperative SSI was iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The interpretation of the higher (nearly twofolds) SSI rate we observed in the ASA score 3/4 group was not shown in another study in patients resected to lung neoplasm 25 . However, several studies had confirmed that the ASA score 3/4 was an independent risk factor for SSI in general surgeries 26–28 …”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The interpretation of the higher (nearly twofolds) SSI rate we observed in the ASA score 3/4 group was not shown in another study in patients resected to lung neoplasm 25 . However, several studies had confirmed that the ASA score 3/4 was an independent risk factor for SSI in general surgeries 26–28 …”
Section: Discussionmentioning
confidence: 62%
“…25 However, several studies had confirmed that the ASA score 3/4 was an independent risk factor for SSI in general surgeries. [26][27][28] Several studies 20,[22][23] had shown that prolonged operating time was an independent risk factor for SSI. This was consistent with our study.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 FRIs occur in approximately 1%-4% of all operative fracture repairs, with a reported incidence as high as 30% for open fractures. [3][4][5] Bacterial seeding of fracturerelated wounds can arise from numerous sources including penetrating trauma, iatrogenic sources, or hematogenous spread. 6 Staphylococci are the most common bacterial genus involved in FRIs, and Staphylococcus aureus is capable of forming biofilms that enable growth on the surface of bone and implants, which can complicate disease eradication.…”
Section: Introductionmentioning
confidence: 99%